Melatih Vocabulary & Daya Listening pada Anak Perantau Negara - Fajar Utama Ritonga; Manda Veronica (Yayasan Literasi Sains Indonesia, 2023)
Childhood is an important period in human life. Because it is during this period that children have strong memories so that they can easily learn and develop from what children see and hear. From an early age, children should be equipped with basic learning so that when they are anywhere, children already have the basic key of knowledge, especially in terms of communicating. Communication is the process of conveying messages from one person to another or to other groups. Good communication is used in the correct, good and appropriate language. Someone who is good at communicating will be easily placed anywhere and won’t get difficulties because they already have mastered the language and how to communicate well. In this discussion, the main subject is the children of overseas countries. As a nomad, the basic key that must be grasped is about language. The more precise language is English because English is a universal language which is used in every country as a communication guide. In fact, there are still many children who haven’t mastered English well so they often get difficulty communicating. The basic problem is due to a lack of knowledge of vocabulary and listening skills. This is causes the child can’t be respond quickly to what the other person is saying, and cannot answer because of the lack of vocabulary. So to facilitate and help children, basic Vocabulary and Listening training activities are carried out. This learning and training is aimed at and carried out for several children of Indonesian citizens whose are in the Philippines. Most of them are forced to be taken overseas by their parents to work because of the lack of income in Indonesia so that they cannot reach their home needs. The purpose of this training would be help the children communicate with the local citizens.